Trestná činnost tzv. bílých límečků - Diviš, Zdeněk (2006)
Subject of the work is an effort to resume problem of criminality of so-called white collars, focusing on the situation in the Czech Republic in last 15 years. The attention was focused first on complete definition of basic terms and reasons, why such criminality occurs, and on definition of the relation between this criminality and other common forms of criminality. The criminal activities of so-called white collars are part of the economic criminality. Fundamental part of the work is dedicated to the problematic of giving evidence.